E-Cigarette Tipping Points Revisited, with Historical Perspective: A Mini Review - Joel L. Nitzkin (Challenges in Disease and Health Research Vol. 7, 2021)
I first visited the issue of e-cigarette tipping points three and a half years ago, in August of 2017. [1] In this paper I revisit this issue, [2] with an eye to what, if anything, had changed since that time. The 2017 paper was written shortly after e-cigarettes appeared to have passed two major tipping points. The first had to do with popularity, with an estimated 10% of the American adult population using or having used e-cigarette products [3]. The second had to do with a perception safety and public health benefit [4]. At the time, I noted that the American Food and Drug Administration (FDA) was projecting a harshly negative view of the safety of e-cigarettes, and, at that time, was only grudgingly acknowledging that there might be personal and public health benefits. Since then, sentiment in the FDA and in the larger American tobacco control community has turned so far against e-cigarettes that each product is now threatened with forced removal from the market unless the manufacturer can promptly submit a “viable” Pre-Market Tobacco Application (PMTA). As previously noted [1], such an application is a physical impossibility for 99% or more of e-cigarette manufacturers because of the cost of the studies required to prepare the application. This essay will address how and why we find ourselves facing the demise of most of the e-cigarette industry in the United States, and what, if anything, should be done about it.